2019
DOI: 10.1093/nar/gkz1158
|View full text |Cite
|
Sign up to set email alerts
|

Myrf guides target gene selection of transcription factor Sox10 during oligodendroglial development

Abstract: Oligodendrocytes generate myelin in the vertebrate central nervous system and thus ensure rapid propagation of neuronal activity. Their development is controlled by a network of transcription factors that function as determinants of cell identity or as temporally restricted stage-specific regulators. The continuously expressed Sox10 and Myrf, a factor induced during late development, are particularly important for terminal differentiation. How these factors function together mechanistically and influence each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…As a member of the HOXB family, HOXB3 was in charge of cell differentiation and proliferation 33 . Besides, MYRF and PLP1 were essential for the oligodendrocytes (OLS) differentiation and myelin maintenance in the central nervous system, which was tightly associated with long‐distance and rapid transmission of nerve electrical impulses 34‐36 . Consistently, we found that the signalling pathways such as myelination and the biosynthesis of differentiation and development of glial cells could promote the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 53%
“…As a member of the HOXB family, HOXB3 was in charge of cell differentiation and proliferation 33 . Besides, MYRF and PLP1 were essential for the oligodendrocytes (OLS) differentiation and myelin maintenance in the central nervous system, which was tightly associated with long‐distance and rapid transmission of nerve electrical impulses 34‐36 . Consistently, we found that the signalling pathways such as myelination and the biosynthesis of differentiation and development of glial cells could promote the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 53%
“…According to the 'de-repression' model of oligodendrocyte development, differentiation-enhancing transcription factors are initially countered by several negative regulators including ID2, ID4, HES5, SOX5, SOX6 and TCF4 [47][48][49]. Interestingly, reciprocal interactions between NKX2.2, OLIG2 and SOX10 have been described [50], as well as between MYRF and SOX10 [51,52]. Hence, oligodendrocyte development reflects a complex interplay between many spatiotemporally orchestrated signals, rather than a simple positive/negative net sum.…”
Section: Transcriptional Network For Opc Differentiationmentioning
confidence: 99%
“…In the absence of a good correlation between effector and target gene expression, we postulate that the interaction with temporally and spatially restricted transcription factors is a major determinant of Sox10 function during involution. The relevance of such interactions for stage-specific Sox10 functions has been documented in other cell types such as oligodendroglia 33 , 34 . Previous studies had shown that miR-424 and miR-503 function downstream of TGF-β during involution 20 .…”
Section: Discussionmentioning
confidence: 95%